2017
DOI: 10.5897/ajar2017.12177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype on yield and yield component of soybean (Glycine max (L) Merrill)

Abstract: In 2013, the multi-location trial was implemented to evaluate the new soybean genotypes for their agronomic performance against the local check. The experiment was conducted in three locations namely Ilonga, Kibaha, and Mlingano in each location a triplicated trial involving six genotypes of soybeans were implemented. The effects of genotype, location and genotype x environment interaction under combined analysis on agronomic yield, and soybean yield were found significant at P<0.05. The highest mean yield was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…It means that the increasing number of pods with 3 seeds is closely related to the increase of seed weight per plant. The results of Lyimo et al (2017) showed that the number of pods per plant was positively and strongly correlated soybean yield. Some researchers (Abady et al, 2013;Aditya et al, 2011;Ngalamu et al, 2013) reported similar results on the importance of the same yield component in determining the yield of soybean seeds.…”
Section: Correlation Between Yield Component and Yieldmentioning
confidence: 97%
“…It means that the increasing number of pods with 3 seeds is closely related to the increase of seed weight per plant. The results of Lyimo et al (2017) showed that the number of pods per plant was positively and strongly correlated soybean yield. Some researchers (Abady et al, 2013;Aditya et al, 2011;Ngalamu et al, 2013) reported similar results on the importance of the same yield component in determining the yield of soybean seeds.…”
Section: Correlation Between Yield Component and Yieldmentioning
confidence: 97%
“…Studies with genetic divergence in this crop were carried out to evaluate the oil content (Peluzio et al 2014), fatty acid content for biodiesel production (Lima and Peluzio 2015), crude protein, oil content and average contents of fatty acids (Rodrigues et al 2017). Studies are also reported in the literature to evaluate the morphological traits and genetic divergence of cultivars in specific cropping regions and conditions, such as genetic dissimilarity in a lowland environment in Tocantins (Almeida et al 2011), first-crop cultivation in the states of Rio Grande do Sul (Rigon et al 2012), Mato Grosso do Sul (Torres et al 2015), and Piauí (Sousa et al 2016), as well as in Tanzania (Lyimo et al 2017). These regional evaluations are important since the soybean crop is responsive to the photoperiod and temperature (Silva et al 2015).…”
Section: Introductionmentioning
confidence: 99%